Aspects of the ecology of the elephant Loxodonta africana (blumenbach, 1797), and a management plan for the Tembe elephant reserve in Tongaland, KwaZulu - Bothma, Jacobus du P. (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 1987.